Greece : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights that Greece has made significant progress in unwinding its macroeconomic imbalances since the onset of its financial crisis. However, extensive fiscal consolidation and internal devaluation have come at a high cost to society, reflected in declining incomes and exceptionally high unemployment. Growth is projected to accelerate in the next few years, conditional on a full and timely implementation of the authorities' adjustment program. On the basis of Greece's current policy adjustment program, long-term growth is expected to reach just under 1 percent, and the primary fiscal surplus is projected to come in at about 1.5 percent of GDP. Downside risks to the macroeconomic and fiscal outlook remain significant.